2016
DOI: 10.1289/ehp135
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Air Pollution Exposures and Risk of Parkinson Disease

Abstract: Background:Few epidemiologic studies have evaluated the effects of air pollution on the risk of Parkinson disease (PD).Objective:We investigated the associations of long-term residential concentrations of ambient particulate matter (PM) < 10 μm in diameter (PM10) and < 2.5 μm in diameter (PM2.5) and nitrogen dioxide (NO2) in relation to PD risk.Methods:Our nested case–control analysis included 1,556 self-reported physician-diagnosed PD cases identified between 1995 and 2006 and 3,313 controls frequency-matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
4
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 40 publications
6
76
4
3
Order By: Relevance
“…When stratified by smoking status, significant associations were observed among former and current smokers, but not among never-smokers. This observation was somewhat contrary to the finding by Liu et al (34), who observed an effect of PM among never-smokers and female never-smokers. However, Liu et al (34) also noted no significant effect of NO 2 among the rural and urban subgroups.…”
Section: No X No 2 Co and "Traffic Air Pollution"contrasting
confidence: 99%
See 2 more Smart Citations
“…When stratified by smoking status, significant associations were observed among former and current smokers, but not among never-smokers. This observation was somewhat contrary to the finding by Liu et al (34), who observed an effect of PM among never-smokers and female never-smokers. However, Liu et al (34) also noted no significant effect of NO 2 among the rural and urban subgroups.…”
Section: No X No 2 Co and "Traffic Air Pollution"contrasting
confidence: 99%
“…Thus, studies sufficiently powered to examine the effects of air pollution on PD risk and progression in specific subgroups, such as nonsmokers, gender-specific groups, and other subgroups relevant to PD are needed. The PAGE study by Liu et al (34) (Table 1), reported significant positive associations between PM 10 and PM 2.5 and the risk of PD in female never-smokers, highlighting the importance of stratified and interaction analyses. Few of the studies included in this review stratified their analyses by gender or smoking [e.g.…”
Section: Interactions With Other Environmental Factors Gene-environmmentioning
confidence: 99%
See 1 more Smart Citation
“…These models showed high cross-validated R 2 , with a national R 2 of 0.88, and well-calibrated predictive intervals. This approach has also been applied in several recent epidemiologic studies of air pollution and health 40,41,42,43,44 . In this work, for each interview year, predictions were made at the census block centroid of respondents’ census blocks of residence, the smallest unit of geography available in the PSID.…”
Section: Methodsmentioning
confidence: 99%
“…54 Although there was not strong evidence for an association between exposures to ambient PM 10 , PM 2.5 , or NO 2 concentrations and risk of Parkinson's disease in older adults, subgroup analyses suggested that female nonsmokers exposed to higher concentrations of PM 10 or PM 2.5 may have a higher risk for Parkinson's disease. 55 …”
Section: Health Effects Analysesmentioning
confidence: 99%